Chromatography Conditions Development by Design of Experiments for the Chemotype Differentiation of Four Bauhinia Species - Aquino, Amanda J.; Pereira-Filho, Edenir R.; Oliveira, Regina V.; Cass, Quezia B. (Frontiers in Chemistry, 2022)
The extensive use of medicinal herbs to traditionally treat disease persists for generations, and scientific evidence on plant-derived extracts has indicated their numerous biological activities. The Bauhinia, popular known as cow's paw (“pata de vaca”), with more than 60 native species, are extensively used in Brazilian popular medicine for the control of diabetes. Therefore, in 2009, B. forficata, B. variegata and/or B. affinis were included in the Brazilian National List of Medicinal Plants of Interest to SUS (RENISUS - Brazil). In this context, this work reports the results of the chemical differentiation of B. forficata, B. variegata, B. longifolia, and B. affinis using liquid chromatography coupled to high-resolution mass spectrometry and unsupervised chemometric tools. Chromatographic conditions were optimized by using the design of experiments (DoE) and chromatographic knowledge. Furthermore, the chemical profile of the studied species was analyzed by principal component analysis (PCA) and hierarchical cluster analysis that differentiated the four species of Bauhinia, and 55 compounds were also inferred by MS2 experiments, some of them for the first time in B. affinis. In this manner, this work provides important information that could be used in quality control, development of new pharmaceuticals, and food products based on Bauhinia leaves, as well as to explain ethnomedicinal properties, pharmacological and toxicological actions.